PENGARUH RASIO AMILUM:AIR DAN SUHU PEMANASAN TERHADAP SIFAT FISIK AMILUM SINGKONG PREGELATIN YANG DITUJUKAN SEBAGAI EKSIPIEN TABLET - Karisma Sari, Kadek Lenny; Anton Prasetia, I G.N. Jemmy; Sri Arisanti, Cok. Istri (Jurnal Farmasi Udayana; Vol. 1, No. 1, Tahun 2012)
Cassava starch is the common type of starch with enormous application in pharmaceutical industries. However, cassava starch has poor compressibility and flowing hard. Therefore, it is need to be modified. One of starch modification methods is physical method like gelatinization because easier than the other method. A good pregelatin starch will be formed by the addition of water and use the proper temperature. This research aimed todetermine the effect ofratio starch:waterandheatingtemperature of cassavastarchtowardphysical characteristic ofpregelatinized cassavastarchintendedasa tabletexcipient. This research was conducted through several stage. First, the manufacture of pregalatinized cassava starch by using ratio starch:water that are 1:0,5 ; 1:0,75, 1:1 and heating temperature are 50°C ; 55°C ; 60°C. Furthermore, cassava starch and pregelatinized cassava starch preliminary tested. Starch which meets the standard then tested their physical properties including moisture testing, particle size distribution test, flow properties test dan compressibility test. Starch with physical properties that meet the requirements then compressed with direct compression method and tested. Testing includes weight uniformity, hardness, friability and disintegrant time. Data were analyzed with one-way ANOVA and LSD with 95% confidence level. The result indicated, the addition of water and heating temperature gives a significance influence (P<0,05) toward the flow characteristic and compressibility of pregelatinized cassava starch. Increasing the amount of water and heating temperature causes decreasing of compressibility. Decreasing of compressibility make flow properties is better. Based on physical properties of test criteria tablet, then selected ratio 1:1 (50 ° C) as selected formula for tablet excipient direct compression method.
Keywords: Pregelatinized cassava starch, flow characteristic andcompressibility